Financial Sector Development and Economic Growth in SSA: Insights with New Data - Amematekpor, I.S. (University Of Ghana, 2018)
This study investigates the empirical relationship between five financial development indicators and economic growth in 25 Sub-Saharan Africa countries from 1980 to 2015 using the broad-based financial development indices of the Global Financial Development Database. The full sample was subsequently divided into three groups: low-income, and lower-middle-income, and high and upper-middle-income SSA countries in order to explore if the level of income influences the impact of finance on growth. The analyses include several panel data econometric techniques that take heterogeneity into account. The Dumitrescu-Hurlin (2012) causality test reveals a short-run bidirectional relationship between the depth of financial institutions and economic growth for the full sample (all) countries. The findings reveal that high and upper-middle-income countries support the supply-leading hypothesis while the low-income and lower-middle-income both follow the demand-following hypothesis. The Westerlund (2005) and Pedroni (1997, 1999, 2004) cointegration tests establish a long-run relationship between financial development and economic growth. The panel Fully Modified OLS and panel Dynamic OLS estimates indicate that financial sector development positively impacts economic growth for all sub-sample groups except for the high and upper-middle-income panel of countries which show negative estimates. Given the importance of financial development, it is recommended that policymakers should urge financial intermediaries to promote access to financial products and services. Also, the regulators of the financial sector must ensure that financial institutions and markets comply with the regulations and guidelines to ensure financial stability. Keywords: Financial development, Economic growth, Sub-Saharan Africa
MPhil
Keywords: Financial Sector; Sub-Saharan Africa; Economic growth; Financial development